2020
DOI: 10.1016/j.curtheres.2020.100605
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ninjin'Yoeito on Fatigue in Patients Receiving Nab-Paclitaxel Plus Gemcitabine Therapy: A Prospective, Single-Arm, Phase II Open Label, Nonrandomized, Historically-Controlled Study

Abstract: Background Ninjin'yoeito , a traditional Japanese herbal medicine, is used to prevent fatigue, loss of appetite, and coldness of limbs. Fatigue is an especially common issue during chemotherapy and can affect quality of life and the ability to complete scheduled treatment. Objectives This prospective exploratory trial evaluates the efficacy of ninjin'yoeito for fatigue in patients undergoing nab-paclitaxel plus gemcitabine thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…There were no complications that affected the treatment of gynecological conditions, such as by prolonging hospitalizations, which indicates that the formula can be used safely. Moreover, NYT has been suggested to be effective not only perioperatively but also as a supportive therapy for managing complications associated with radiation and chemotherapy [ 23 – 25 , 44 , 61 ]. As it can provide a comprehensive treatment at any stage of patients with gynecological diseases, it has been concluded as a promising Kampo formula.…”
Section: Discussionmentioning
confidence: 99%
“…There were no complications that affected the treatment of gynecological conditions, such as by prolonging hospitalizations, which indicates that the formula can be used safely. Moreover, NYT has been suggested to be effective not only perioperatively but also as a supportive therapy for managing complications associated with radiation and chemotherapy [ 23 – 25 , 44 , 61 ]. As it can provide a comprehensive treatment at any stage of patients with gynecological diseases, it has been concluded as a promising Kampo formula.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Hozai is effective for treating fatigue because of its immune-stimulatory effects [ 8 , 9 , 14 , 15 ]. However, no study has focused on the differences among HET, JTT, and NYT or those among these agents from different pharmaceutical industries in Japan, including their immunological effects on PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, JTT increases the regulatory activities of T cells by decreasing the forkhead box p3 (Foxp3) + regulatory T cell (Treg) population in patients with advanced pancreatic cancer [ 8 ]. The symptoms of fatigue caused by nab-paclitaxel plus gemcitabine treatment administered to patients with unresectable pancreatic cancer have been reported to be improved by NYT [ 9 ]. Furthermore, NYT has been shown to synergistically enhance the effects of a tumor vaccine mediated by CD8 + T cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it translates to "ginseng nutritive decoction," based on its main ingredient, it is known to improve the nutritional status and used as herbal medicine for symptomatic treatment of "post-illness weakness, fatigue, loss of appetite, night sweats, cold extremities, and anemia." Previous clinical and preclinical studies concluded on its effectiveness in anemia [17,18], fatigue [19][20][21][22][23][24][25], and psychological conditions, namely anxiety and depression, as well as lethargy and apathy associated with Alzheimer's and Parkinson's diseases [26][27][28][29][30]. However, very little prospective research has been performed to investigate the effects of administering NYT in patients having preoperative anemia with unspeci ed symptoms, especially for gynecological diseases.…”
Section: Introductionmentioning
confidence: 99%